Sosialisasi dan Edukasi Pentingnya Manajemen Perubahan dalam Pendidikan di SD YPK Muli - Nirtha, Eva; Au Hurit, Andreas; Hanip, Rival (Universitas Majalengka, 2025)
This community service activity aims to provide socialization and education about the importance of change management in education at SD YPK Muli Merauke. This activity was attended by 12 teachers and one principal. The resource person, Mr. Andreas Au Hurit, delivered material on effective change management strategies in the educational environment. During the activity, there was active interaction in the form of questions and answers and discussions between participants and resource persons. Based on observations, the teachers were very enthusiastic in participating in this activity. In addition, the results of the reflection sheet showed that the teachers were happy and hoped that similar programs could be continued in the future. The principal also gave positive support to the continuation of this program, considering the importance of change management in improving the quality of education in schools. Keywords: Socialization, Education, Change Management